Avaliação da qualidade dos serviços prestados em escolas públicas de ensino fundamental II e médio da cidade de Paracatu/MG - (:unkn) unknown (Universidade Federal de Goiás, 2019)
This research is based on the study of the satisfaction of internal and external users of two school institutions, the Cacilda Caetano de Sousa Municipal School and the Altina de Paula Guimarães State School, in relation to the services provided. It is an applied research with quantitative approach, which had its data collected through the users' perspectives regarding their expectations and perceptions of services regarding the five dimensions of quality described in the Servqual instrument model (tangible elements, reliability, promptness, security and empathy). The main objective of this study was to evaluate the quality of services provided at both institutions and to know if there is a significant difference regarding the dimensions between each participant group and between each school. The methodology used for research and data collection was the application of two questionnaires - Servqual model - to each participant, one to evaluate expectations and the other the perceptions regarding the 22 variables distributed in the five quality dimensions; In addition to these 22 questions, some socio-demographic and other questions that assessed other criteria were also applied, including the degree of importance among the dimensions for the services to be provided with quality. For data analysis we used statistical tests as measures of central tendency (average), standard deviation, coefficient of variation, quartiles and Anova. Through the results of these tests the analyzes were made and the degree of satisfaction of the participants was evaluated by calculating the gap (differences between expectation and perception) and the correlations between each result. As a result the systematization is composed of a sequence of results for each dimension that will support those who are interested in identifying the gaps, checking which gaps are having very negative results and in more critical states, and thus, from the results. Each dimension should check why and apply actions to alleviate or even try to close these identified gaps that are interfering with the quality of the services provided
Evaluation of quality of services provided in public schools of fundamental II and average city of Paracatu / MG
Keywords: Qualidade; Satisfação; Serviços prestados; Instituição de ensino; Servqual; Quality; Satisfaction; Services provided; Educational institution; Servqual; ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS